2016
DOI: 10.1186/s12879-016-1926-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of viral suppression and rebound among HIV-positive men who have sex with men in a large multi-site Canadian cohort

Abstract: BackgroundGay, bisexual and other men who have sex with men (MSM) are disproportionately affected by HIV in Canada. Combination antiretroviral therapy has been shown to dramatically decrease progression to AIDS, premature death and HIV transmission. However, there are no comprehensive data regarding combination antiretroviral therapy outcomes among this population. We sought to identify socio-demographic and clinical correlates of viral suppression and rebound.MethodsOur analysis included MSM participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 38 publications
9
33
0
Order By: Relevance
“…These factors have also been reported in previous studies. 2,3 Of note, the authors also found that black African men and women had higher rates of viral rebound, a finding that was also shown in a study investigating protease inhibitor monotherapy in the UK. 4 Lower initial rates of viral suppression after starting ART have been commonly reported in African Americans 5 and Indigenous communities in Canada, 6 but not in Aboriginal people in Australia.…”
mentioning
confidence: 59%
“…These factors have also been reported in previous studies. 2,3 Of note, the authors also found that black African men and women had higher rates of viral rebound, a finding that was also shown in a study investigating protease inhibitor monotherapy in the UK. 4 Lower initial rates of viral suppression after starting ART have been commonly reported in African Americans 5 and Indigenous communities in Canada, 6 but not in Aboriginal people in Australia.…”
mentioning
confidence: 59%
“…As expected we found a significant interaction between the two laboratory variables (CD4+ counts and HIV-1 RNV viral load). Baseline CD4+ count (cells/mm 3 ) is predictive of virologic failure and AIDS-related mortality 36,37 and, due to the strong interaction between these two laboratory variables, we decided to exclude HIV-1 RNA viral load from our final model. We also identified a significant interaction between education and ethnicity, and decided to include it in our final models ethnicity instead of education level as the key socioeconomic status variable.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cell-associated (CA) HIV-1 RNA has been demonstrated to predict ART failure and to correlate with adherence to therapy in virologically suppressed individuals (2,3), indicating that this marker could be of use in clinical care of individuals on otherwise-suppressive ART because it is more sensitive than plasma VL for associations with certain clinical endpoints. Pre-ART plasma VL, CD4 + T cell count, and total HIV-1 DNA have been shown to predict the rates of virological suppression on ART (4)(5)(6). However, to the best of our knowledge, the predictive value of CA RNA for the response to ART has not yet been reported.…”
Section: Introductionmentioning
confidence: 94%